2013
DOI: 10.1590/s0100-06832013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nickel and nitrogen soil fertilization on lettuce growth and urease activity

Abstract: SUMMARYNickel is a micronutrient involved in nitrogen metabolism and a constituent of the urease molecule. Plant growth and urease activity were evaluated in lettuce (Lactuca sativa L.) grown in soil-filled pots in a 2 x 8 factorial design with two nitrogen (N) sources and eight Ni rates, with five replications. Nitrogen was applied at 200 mg dm -3 (half the dose incorporated into the soil at seedling transplanting and half top-dressed later) using the sources NH 4 NO 3 (AN) and CO(NH 2 ) 2 (Ur). The Ni treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
(26 reference statements)
1
1
0
1
Order By: Relevance
“…The fact that the urease activity was highly correlated with the concentration of nickel in its most available form (Fig. 3a), is not surprising and can be expected if based on the results of the data in literature (Marschner 1995;Vahed et al 2011;Oliveira et al 2013;Zhang et al 2014). However, the second strongly positive correlation found in our experiments, between the urease activity and the nickel content in the socalled residual form (Fig.…”
Section: Resultssupporting
confidence: 52%
“…The fact that the urease activity was highly correlated with the concentration of nickel in its most available form (Fig. 3a), is not surprising and can be expected if based on the results of the data in literature (Marschner 1995;Vahed et al 2011;Oliveira et al 2013;Zhang et al 2014). However, the second strongly positive correlation found in our experiments, between the urease activity and the nickel content in the socalled residual form (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Interestingly, the addition of Ni—the urease co‐factor present in several silicate materials—may aid in this regard. Laboratory studies have shown that supplementation of Ni to the soil increased the health and growth rate of lettuce plants (Khoshgoftarmanesh et al, 2011; Oliveira et al, 2013). Adding silicate materials containing Ni may thus stimulate biomineralization of CaCO 3 by urease, and hence C sequestration (Bachmeier et al, 2002), while at the same time stimulating plant growth and reducing urea volatilization.…”
Section: Biota Stimulating Silicate Weatheringmentioning
confidence: 99%
“…Autores como Oliveira (2013), constataram aumento da atividade da urease em folhas de alface com a utilização de doses de níquel, e Rodak et al (2012) observaram, com o níquel, também um incremento na produção da soja. Todavia, relataram aumento de Ni nas folhas ao aplicar fertilizantes à base deste, porém não verificaram aumento na produção da soja.…”
Section: Introdução Geralunclassified